2015
DOI: 10.1055/s-0035-1567827
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Arising in an HNF-1α–Mutated Adenoma in a 23-Year-Old Woman with Maturity-Onset Diabetes of the Young: A Case Report

Abstract: Hepatocyte nuclear factor-1α mutated hepatocellular adenomas (H-HCA) are thought to have no to minimal malignant potential. This report describes a 23-year-old woman with maturity-onset diabetes of the young who developed a 12.5-cm hepatic mass with a radiographically and pathologically distinct 3.0-cm region. Histologically and immunohistochemically, the bulk of the mass was an H-HCA with extensive pseudoglandular formation and only focal steatosis. The 3.0-cm nodule showed small cell change, thickened hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Finally, according to the recent literature, H-HCA almost never degenerate into HCC, although some very rare cases have been reported [ Stueck et al 2015 ]. The low risk of H-HCA degeneration may help to simplify the management of liver adenomas as will be discussed later.…”
Section: Reviewing the Known Complicationsmentioning
confidence: 99%
“…Finally, according to the recent literature, H-HCA almost never degenerate into HCC, although some very rare cases have been reported [ Stueck et al 2015 ]. The low risk of H-HCA degeneration may help to simplify the management of liver adenomas as will be discussed later.…”
Section: Reviewing the Known Complicationsmentioning
confidence: 99%
“…Because HHCAs showed the lower risk of malignant transformation, typical features of small H-HCAs at MRI in young women could avoid biopsy and lead to radiologic follow-up [ 36 , 63 ]. It should be emphasized that HCC can arise also in these lesion, as recently reported [ 64 ]. In the absence of typical features of H-HCA at MRI, a tumor biopsy should be proposed to search for β-catenin activation/mutation and to better assess the risk of malignant transformation [ 33 , 36 , 43 ].…”
Section: Hepatocellular Adenoma (Hca)mentioning
confidence: 54%
“…For the molecular changes and tumor biomarkers of HCC, the authors found that by immunohistochemical tests, CD34 expression in sinusoidal endothelial cells and expression of glutamine synthetase in tumor cells were increased, whereas exon 3 of CTNNB1 and TERT promoter mutations, and nuclear expression of β-catenin were absent in this patients with HCC and DM. Although such cases are rare, they reinforce the potential of H-HCA for HCC, which may be related to DM[ 98 ].…”
Section: Mpe In Dm and Risk Of Hccmentioning
confidence: 99%
“…One case report which was published in 2015 was also considered to be related to this field[ 98 ]. This report describes a 23-year-old woman with HCC and type 2 DM; and results of histological and immunohistochemical examination showed that this HCC arose in the background of hepatocyte nuclear factor-1α mutated hepatocellular adenomas (H-HCA).…”
Section: Mpe In Dm and Risk Of Hccmentioning
confidence: 99%